Peace Education and its Role in Family Stability and Sustainable Cohesion among Rural Dwellers in Ezinihitte Mbaise, Imo State Nigeria - Rophina Ifeyinwa Chima Ehumadu (International Journal of Home Economics, Hospitality and Allied Research)
The study focused on Peace Education and Its Roles in Family Stability and Sustainable Cohesion among Rural Dwellers in Ezinihitte Mbaise, Imo State. Its specific objectives were to identify the various ways peace education programme has stabilized families and infused sustainable cohesion of rural dwellers in Ezinihitte Mbaise. The study identified problems encountered by agents/staff in disseminating peace education information to the rural dwellers in Ezinihitte Mbaise and recommended solutions to the problems. It adopted survey design using descriptive statistics mean for data analysis. The population of the study comprised all Ezinihitte Mbaise rural dwellers numbering 234,600 from the 29 autonomous communities of the area. The sample was 399 purposively selected through simple random sampling from the population using Taro Yamane formula. A mean ratio of 2.50 based on four point scale was accepted. Findings identified various ways peace education programme has established stability and impacted sustainable cohesion in families of rural dwellers in the study area. It was recommended, among others, that appropriate agents/staff, with assistance from governments, should organize seminars, symposia and workshops for all rural dwellers to create awareness on the importance of peace education generally; employ qualified staff and provide necessary equipment and transportation logistics to facilitate teaching and learning of peace education especially in rural communities. The study concluded that provision of these logistics will enable stakeholders imbibe proper dissemination techniques as well as acquire necessary knowledge, values, skills, and attitudes required for cohabitation and family stability that will impact sustainable cohesion among rural dwellers and foster peace education globally.